2018
DOI: 10.3126/jmmihs.v4i1.21133
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic lesions: Histopathological study in a tertiary care hospital

Abstract: Background: Prostatic lesions like Nodular hyperplasia of prostate, inflammation and carcinoma are common causes of morbidity and mortality in males. The incidence of these lesions increases with age. This study was conducted with the objective of evaluating histopathological pattern of prostatic lesions.Methods: This was a retrospective study conducted at KIST Medical College from Jan 2014 to Jan 2018. The study included ninety six prostatic specimens received in department of pathology. Hematoxylin and Eosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 10 publications
4
11
0
Order By: Relevance
“…Our findings are comparable with other studies done by Bhatta S et al [16] and Deshmukh et al [15] . (Table 5).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are comparable with other studies done by Bhatta S et al [16] and Deshmukh et al [15] . (Table 5).…”
Section: Discussionsupporting
confidence: 93%
“…Rajani D from India reported similar findings in 2020 (1). Similar pattern of lesions was reported by different studies done by Shah, Hussain AG from Iraq, Josephine A, Neha A, Bhatta S, Yadav M (11)(12)(13)(14)(15)(16). Testosterone hormone causes the hypertrophy of the gland by binding to DHT receptors in prostate (2).…”
Section: Discussionsupporting
confidence: 57%
“…21 Bhatta S et al in their study found PNI in 37.5% cases. 17 In our study, lymphovascular invasion (LVI) was noted in 30% case and high Gleason's score 9 (20%). May M et al in their study stated that LVI was seen in 10.2% cases with high PSA, 79% of cases had a Gleason score of > or = 7.…”
Section: Discussionmentioning
confidence: 51%
“…Bhatta S et al stated most common grade group in their study was grade group 4 and the most predominant Gleason score was 9, which indicated poor prognosis. 17 Gleason score of 9 was seen in 3 out of 8 cases (37.5%). A study by Deshmukh BD et al found Gleason score 9 in 33.33% cases.…”
Section: Discussionmentioning
confidence: 93%